Development of a novel technology to immobilise enzymes in the mesoporous Zr02 matrix and applications in the large scale asymmetric resolution of chiral compounds - Ching, Chi Bun. (2010)
Our study has demonstrated for the first time that zirconia nanoparticles modified by a simple carboxylic surfactant of a very long alkyl chain can significantly enhance the activity of the immobilized lipases for asymmetric synthesis in organic media. Zirconia nanoparticles of ca. 20 nm in diameter were grafted with carboxylic surfactant modifiers from Tween 85 and erucic acid. The surface of nanoparticles was successfully changed from hydrophilic to hydrophobic. Lipases from Candida rugosa and Pseudomonas cepacia were immobilized on the modified zirconia nanoparticles by adsorption in aqueous solution. The immobilized lipases were used for the resolution of (R,S)-ibuprofen and (R,S)-1-phenylethanol through esterification and acylation, respectively, in isooctane organic solvent. When immobilized on erucic acid modified zirconia, both lipases gave significantly higher activity and enantiomeric excess compared with those from their corresponding crude lipase powders. The nanohybrid biocatalysts are stable and can be reused for eight cycles without loss in activity and selectivity. The interaction between the hydrophobic surface of zirconia support and lipases probably induces the conformational rearrangement of lipases into an active and stable form.